Teacher Professional Learning Community’s Creation and Development Factors - Monkevičius, Justinas (Pedagogika, 2017)
Article analyses teacher professional learning communities (TPLC’s) creation and development factors. Literature research revealed the lack of theoretical approach of TPLC’s creation and development factors. Thus, grounded research theory is used in order to further analyze TPLC’s creation and development factors. Structured interview with school teachers and administration was conducted until it reached theoretical saturation. Analysis of literature research revealed Personal, interpersonal and managerial school’s principal and personal, interpersonal and managerial school’s teacher factors as very important ones. During empirical research schools’ principals and teachers identified factors having positive effect to TPLC’s creation and development in their own environment. Article analyses theoretical and empirical differences of PLC’S creation and development factors.